Pathogens in fish from natural and farmed environments in the State of Maranhão: An overview and perspectives for research (Research, Society and Development, 2021)
In the search for knowledge about fish health, understanding ecological interactions is essential, but for a long time there was neglect in studies on parasites that affect them. The work with fish pathogens in the State of Maranhão is still insufficient and for this reason this work comes with the objective of conducting a survey of scientific researches developed in the period from 2010 to 2020 on those of pathogens in fish from natural environments and from cultivation of this state. The systematic search for scientific articles on the Web of Science, Google Scholar, Pubmed, ASFA, Scopus and SciELO platforms was used as methodological strategies, in the period from 2010 to 2020, in order to gather information on the topic under study. The results were separated by category of etiological agents due to the diversity of classes and different techniques used in the surveys surveyed. The data obtained show that the fish may be affected by ectoparasitic crustaceans, bacterioses, nematodes, protozoa, myxosporids, fungi, monogenoids and viruses, however in Maranhão the research with these fish parasites is still incipient, in this sense the need for more studies on fish health in this region. In addition, detailed studies on the life cycle of parasites and their transmission routes in order to prevent infections, as well as the construction of an action plan with treatment, control and prevention strategies for these pathologies will be of great relevance in future studies and environmentally sustainable.